Theoretical analysis of GOMP based on RIP and ROC - Li, Haifeng; Guo, Leiyan (Japan journal of industrial and applied mathematics, 2024)
This paper aims to investigate sufficient conditions for the recovery of sparse signals via the generalized orthogonal matching pursuit (gOMP) algorithm. In the noisy case, a sufficient condition for recovering the support of k -sparse signal is presented based on restricted isometry property (RIP) and restricted orthogonality constant (ROC).